(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses the main aspects of capital management and the financial support process in an organization. The key principles of capital management are described, including optimization of its structure, effective management of working capital and management of investment projects. The financial assurance process is also presented, which covers raising finance, managing debt obligations and using financial resources. In conclusion, the article offers practical steps for capital and financial management, such as analyzing a company’s financial condition and developing a capital management strategy.